2008
DOI: 10.1007/s00167-007-0474-x
|View full text |Cite
|
Sign up to set email alerts
|

“Biological failure” of the anterior cruciate ligament graft

Abstract: Anterior cruciate ligament (ACL) reconstruction has the best chance for success when the graft undergoes extensive biologic remodeling and incorporation after implantation. There are many factors that can lead to graft failure and possible revision surgery. These include patient selection; surgical technique such as graft placement and tensioning; the use of allograft versus autograft; mechanical factors such as secondary restraint laxity; lack of a correct, carefully controlled post-operative rehabilitation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
139
1
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 49 publications
0
139
1
13
Order By: Relevance
“…First, mechanical factors such as secondary restraint laxity may influence knee stability or function [17]. There is a paucity of published information concerning the relationship between knee hyperextension and stress concentration on the reconstructed ACL.…”
Section: Discussionmentioning
confidence: 99%
“…First, mechanical factors such as secondary restraint laxity may influence knee stability or function [17]. There is a paucity of published information concerning the relationship between knee hyperextension and stress concentration on the reconstructed ACL.…”
Section: Discussionmentioning
confidence: 99%
“…Además, se observó un aumento de cambios degenerativos en el compartimento lateral de la rodilla (85,86) . Posteriormente, se pasó a la reconstrucción intraarticular transtibial del LCA mediante fascí-culo único, convirtiéndose en el gold estándar, con una orientación más vertical de la misma, mejorando en este caso la inestabilidad anteroposterior, pero con resultados pobres en el control de la inestabilidad rotacional (87,88) . En un afán de mejorar este control rotacional se comenzaron a realizar reconstrucciones con doble fascículo del LCA (89)(90)(91) .…”
Section: Tratamientounclassified
“…By meta-analysis, Kraeutler et al 25 assessed the knee stability after ACL reconstruction with autografts or allografts, and concluded that there was a lower level stability in the allograft group. The etiology of knee instability caused by the allograft is multifactorial, and accumulating evidences suggest that sterilization and preservation of the allograft 26 and immunological factors 27 are involved. The allograft that we used went through the process of irradiation, freezing, and thawing, which could affect their structural and mechanical properties.…”
Section: Acta Cir Bras 2017;32(12):1064-1074mentioning
confidence: 99%